A case report of pericardial constriction with coexisting severe left main coronary artery disease. Issue 7 (2nd July 2022) - Ostad Karampour, Saman; Sedlak, Tara L; Luong, Christina L; Price, Joel E; Brunner, Nathan W
Abstract: Background: Constrictive pericarditis (CP) is a rare condition in which the pericardium becomes progressively fibrotic and non-compliant leading to impaired ventricular filling and overt heart failure. While CP shares many clinical and haemodynamic similarities with restrictive cardiomyopathy, differentiation of these diseases is crucial as CP is potentially curative through pericardiectomy. Here, we present a case of proven pericardial constriction with atypical haemodynamics in a patient presenting with heart failure and severe left main coronary artery disease (CAD). Case summary: A 69-year-old female with a history of hypertension and paroxysmal atrial fibrillation presented with persistent heart failure refractory to diuretics. Ischaemic and infiltrative work-up were found to be negative with magnetic resonance imaging demonstrating trace pericardial fluid and thickening of the pericardium. Echocardiogram and right-heart catheterization demonstrated atypical haemodynamics suggestive of but not conclusive for CP, with coronary angiogram demonstrating severe left main CAD. Ultimately, the patient underwent coronary artery bypass grafting along with pericardiectomy and pericardial biopsy demonstrating constrictive physiology. Discussion: We suspect the inconclusive nature of the echocardiogram and cardiac catheterization was likely secondary to severe CAD impairing left ventricular relaxation and dampening ventricular interdependence. As such, clinicians should consider the possibility of coexistent severe CAD in patients with a clinical suspicion of CP, but inconclusive haemodynamics.